Geometrija trikotnika, Oroslan in Ravello - Hvala, Bojan (Obzornik za matematiko in fiziko, 2021)
In this article, we present Seebach’s theorem, which is a topic in triangle geometry. The events, as during guided online film screenings, take place on two channels. On one, there is a mathematical presentation of the topic, and on the other, a chat about possibilities, dilemmas, and backgrounds.
Keywords: geometrija; trikotnik